The Initiation-Response-Feedback (IRF) Model and Repair Strategies in Classroom Interaction - Hilma Adzkia (STKIP AL HIKMAH SURABAYA, 2025)
Effective teacher-student interaction is fundamental to language learning, particularly in English as a Foreign Language (EFL) classrooms. One prominent framework for analyzing classroom discourse is the Initiation-Response-Feedback (IRF) model, which highlights the structured nature of teacher-led interactions A summary of a review of foreign language learning for elementary school students regarding recognizing the names of fruits and constructing sentences with the names of these fruits is a good start to learning a foreign language, where students are given a lot of vocabulary as initial capital for them to compose sentences and speak, while the role of the teacher Here, apart from being a material provider, the teacher also becomes a judge who is able to reflect on what students do and provide feedback that builds students to learn English better